Mechanochemical Properties of Mucoadhesive Tablets Based on PVP/HPβCD Electrospun Nanofibers as Local Delivery of Polygoni cuspidati Extract for Treating Oral Infections - Magdalena Paczkowska-Walendowska; Daria Szymanowska; Judyta Cielecka-Piontek (MDPI AG, 2023)
This study investigated the ability of PVP/HPβCD-based electrospun nanofibers to enhance the dissolution rate of poorly soluble polydatin and resveratrol, the main active components of Polygoni cuspidati extract. To make a solid unit dosage form that would be easier to administer, extract-loaded nanofibers were ground. SEM examination was used to analyze the nanostructure of the fibers, and the results of the cross-section of the tablets showed that they had maintained their fibrous structure. The release of the active compounds (polydatin and resveratrol) in the mucoadhesive tablets was complete and prolonged in time. Additionally, the possibility of staying on the mucosa for a prolonged time has also been proven for both tablets from PVP/HPβCD-based nanofibers and powder. The appropriate physicochemical properties of the tablets, along with the proven antioxidant, anti-inflammatory, and antibacterial properties of P. cuspidati extract, highlight the particular benefits of the mucoadhesive formulation for use as a drug delivery system for periodontal diseases.